Maternal and early life factors of tooth emergence patterns and number of teeth at 1 and 2 years of age. (4th May 2015) - Ntani, G.; Day, P. F.; Baird, J.; Godfrey, K. M.; Robinson, S. M.; Cooper, C.; Inskip, H. M.
Abstract : Various environmental factors have been associated with the timing of eruption of primary dentition, but the evidence to date comes from small studies with limited information on potential risk factors. We aimed to investigate associations between tooth emergence patterns and pre-conception, pregnancy and postnatal influences. Dentition patterns were recorded at ages 1 and 2 years in 2915 children born to women in the Southampton Women's Survey from whom information had been collected on maternal factors before conception and during pregnancy. In mutually adjusted regression models we found that: children were more dentally advanced at ages 1 and 2 years if their mothers had smoked during pregnancy or they were longer at birth; mothers of children whose dental development was advanced at age 2 years tended to have poorer socioeconomic circumstances, and to have reported a slower walking speed pre-pregnancy; and children of mothers of Asian ethnicity had later tooth development than those of white mothers. The findings add to the evidence of environmental impacts on the timing of the eruption of primary dentition in indicating that maternal smoking during pregnancy, socio-economic status and physical activity (assessed by reported walking speed) may influence the child's primary dentition. Early life factors, including size at birth are also associated with dentition patterns, as is maternal ethnicity.